(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Women seeking medical attention at the Tashkent City Oncology Dispensary due to mastopathy account for 55-60% of the total number of patients from the Chilonzor, Uchtepa, and Shaykhontokhur districts. This situation does not indicate that the disease is more common in certain districts, but rather may reflect a higher level of medical awareness among the population. When studying the seasonality of mastopathy, it was found that most cases occur in the spring and autumn.